Consciousness, Creativity, and Freedom: On the Creative and Free Nature of Consciousness in the Bohm-Biederman Correspondence - Béjar Gallego, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The fluid correspondence between the physicist David Bohm and the artist Charles Biederman in the sixties on the creative nature of human consciousness shows the origin of a new epistemological paradigm in the history of thought in the twentieth century. Against the positivist schools about the subject and object, which cannot agree integrally with phenomenological conscious experience, Bohmand Biederman tried to adapt the dominant epistemologies in science and art to the ontological realism perceived by human beings. Their letters are full of metaphysical intuitions on consciousness, creativity and human freedom. This article presents and comments on some of the most important metaphysical ideas in their published letters, and explains them in the context of their respective epistemological frameworks.
Keywords: mind; determinism; structurism; intuition; holism; quantum physics